Strategi Belajar Think Talk Write dan Kemampuan Berpikir Logis Matematis - Pratiwi, Reni Septia; Kustati, Martin; Susanto, Andi (Math Educa Journal, 2019)
The purpose of this study was to find out the logical thinking skills of students who learn with Solok City's Solok Think Talk Write class VIII strategy. This research is a quasi-experimental design with Randomized Control Group Only Design. Random sampling technique. The experimental class VIIIG and the VIIIE control class were selected. The instrument of this study tests mathematical logical thinking skills. Based on the results of the test, the average experimental class was 80.81 higher than the control class of 75.03. Hypothesis testing with t-test shows that mathematical logical thinking ability of experimental class students is higher than control class students.